2020
DOI: 10.1111/nup.12329
|View full text |Cite
|
Sign up to set email alerts
|

Giving a voice to patient experiences through the insights of pragmatism

Abstract: As a philosophical position, pragmatism can be critiqued to distinguish truth only with methods that bring about desired results, predominantly with scientific enquiry. The article hopes to dismiss this oversimplification and propose that within mental health nursing, enquiry enlightened by pragmatism can be anchored to methods helping to tackle genuine human problems. Whilst pragmatists suggest one reality exists, fluctuating experiences and shifting beliefs about the world can inhabit within; hence, pragmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Another study, based in the United Kingdom, examined the role of pragmatism in nursing and captured how beneficial pragmatism could be in the mental health setting (Deering et al, 2021). Deering et al (2021) discussed three themes found in pragmatism: plurality, fallibility and meliorism. They discussed the constant tension around the question of who has the knowledge (Deering et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another study, based in the United Kingdom, examined the role of pragmatism in nursing and captured how beneficial pragmatism could be in the mental health setting (Deering et al, 2021). Deering et al (2021) discussed three themes found in pragmatism: plurality, fallibility and meliorism. They discussed the constant tension around the question of who has the knowledge (Deering et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Prudence is a governing virtue, suggesting that an agent would be of merit to arrive at pragmatism. An agent who leads, generates meaning, who casts light on woman-centred care points of view and actions, who shifts the direction of ideas in maternity services and who safeguards the essence and importance of womancentred care (Deering et al, 2020;McInnes et al, 2020).…”
Section: Prudencementioning
confidence: 99%
“…Functioning as a woman-centred care (student) midwife begins within the social context of woman-centred care midwifery and requires pragmatism, through seeking and creating experiences that shape the utility of woman-centred care, envisaging the truth of woman-centred care and discarding its errors (Deering et al, 2020).…”
Section: A Sketch Of Pragmatic Midwifery Socialization and Transforma...mentioning
confidence: 99%
“…Abductive reasoning is understood as the faculty of examining a set of facts and permitting for those events to imply a theory, for which is considered accumulated experience, given that the theory cannot be generated without a prior context or a surprising nursing phenomenon. (14) From the approaches of the classics Peirce and Dewey, referenced by Deering (11) and Moscoso (14) allowed to build the components of abductive reasoning so that they could be applied and characterized to nursing practice because they can occur simultaneously or in different moments; however, it is necessary that all occur in the same situation. These are defined briefly in the following:…”
Section: Components Of Abductive Reasoning For the Nursing Practicementioning
confidence: 99%
“…Experiences are part of reality, but it has the potential to change and be influenced by the context upon demonstrating certain degree of utility for science and society. (11) Because nursing is of pragmatic nature, it could be stated that the development of this discipline is also pragmatic. In other words, the nursing setting transcends from a context of theoretical application to one of generation of knowledge.…”
Section: Introduction Imentioning
confidence: 99%